Pore‑fluid‑dependent controls of matrix and bulk thermal conductivity of mineralogically heterogeneous sandstones - Kämmlein, Marion; Stollhofen, Harald (Geothermal Energy, 2019)
For a variety of geothermal engineering applications, the only indirectly determinable matrix thermal conductivity (λm) is frequently used to convert the measured bulk rock thermal conductivity (λb) of air-saturated sandstones to water-saturated conditions. However, the necessary assumption that the absolute value of λm remains constant irrespective of the pore fluid present turns out to be not valid in practice and the explicit control factors on λm have not been demonstrated yet for different pore fluids. A pore fluid-controlled change in the λm value also questions the transferability of empirical proxy models for the estimation of water-saturated λb when they were calibrated on air-saturated samples. This study applies a multiple regression analysis to quantitative mineralogical composition data and porosity (Φ) to identify the controls of the λm for different types of pore fluids (water- vs. air-saturation). In addition, the differences in the calculated λm values resulting from different calculation methods or input data (theoretical geometric mean model or mineralogical composition data) are examined. We further test the suitability of different sandstone properties as potential proxies for the estimation of the λb, with respect to the pore fluid type. Differences in the absolute value of λm of sandstones from different measurement conditions (air- or water-saturated) are most probably related to the formation of authigenic kaolinite in the pore space, originating from the alteration of alkali feldspar. In addition, the thermal properties of the rock matrix are mainly controlled by the volume fractions of the high thermally conductive mineral fractions quartz and dolomite. Empirical models that have solely Φ or P-wave velocity (vp) as variables are not suitable for the prediction of water-saturated λb of sandstones. Instead, quantitative mineralogical data of high thermally conductive mineral phases such as quartz and dolomite have to be included. The easily measureable vp is proposed as a promising proxy for both pore fluid types tested: combined with the total quartz volume/porosity ratio for air-saturated sandstones, and combined with the quartz plus dolomite volume fractions for water-saturated sandstones.<br
Keywords: Matrix thermal conductivity; Bulk thermal conductivity; Pore fluid; Sandstone; Mineralogical composition; Anisotropy